Manners, Social Behavior and Freedom of Speech: From Henry James to the European Convention on Human Rights1 - Porsdam, Helle (Academic Quarter | Akademisk kvarter, 2012)
The article discusses the question whether freedom of speech is unlimited or not. With the point of departure in article 10 of the Euro¬pean Convention on Human Rights (ECHR) which first mentions “the right to freedom of expression,” but then immediately narrows this right, the article moves on to the American writer Henry James, who was preoccupied with this necessity to guard against hateful remarks. And one of the conclusions of the article is that James tried to teach us the importance of manners and speech as tools in the service of defusing violently tense political and social situations. As he saw it, communicative and social skills could lead the way toward a stable, multicultural democracy and provide the necessary cultural glue.